Treatment strategies in human papillomavirus-related advanced penile cancer - Longoni, Mattia; Fankhauser, Christian D; Negri, Fausto; Salonia, Andrea; Basile, Giuseppe; Johnstone, Peter A S; Bandini, Marco (Nature reviews. Urology, 2025)
Penile cancer is a rare neoplasm with heterogeneous prevalence influenced by risk factors such as smoking, poor hygiene and human papillomavirus (HPV) infection. Southern Africa, South America and Southeast Asia have the highest incidence of this disease. Penile squamous cell carcinomas (PSCCs) account for the majority of instances of penile cancer, with HPV-related carcinogenesis implicated in up to half of them. Increases in PSCC incidence in industrialized nations parallel the rising high-risk HPV infection rates, particularly HPV-16. Early-stage, localized PSCC is often manageable, but treatment options in advanced disease remain limited, with poor survival outcomes. Emerging evidence suggests that HPV-positive PSCC might exhibit unique therapeutic responses, including increased sensitivity to radiotherapy and chemotherapy, as has been observed in HPV-driven head and neck squamous cell carcinoma. Results of studies in HPV-positive PSCC demonstrate improved responses to chemoradiotherapy and immunotherapy, underscoring the potential for tailored treatments and de-escalation. Additionally, incorporating immunotherapy with radiotherapy in HPV-driven PSCC might provide greater oncological benefits than standard chemotherapy. These observations suggest that treatment strategies for HPV-positive PSCC might benefit from de-escalated chemoradiotherapy regimens or immunotherapy incorporation, potentially optimizing efficacy while minimizing toxic effects. Furthermore, biomarkers such as tumour mutational burden, programmed cell death ligand 1 expression, and genetic alterations could be crucial for predicting treatment response. Comprehensive biomarker assessment and accurate HPV status determination are essential for developing patient-tailored therapeutic strategies. These data provide evidence of the potential benefits of individualized approaches based on tumour biology and biomarker profiles.